Adaptive Selling, Personal Selling, and Selling Experience on the Service Personnel Performance - Ni Made Rianita (Universitas Pendidikan Ganesha, 2022)
The number of complaints from service users who repeatedly come to PT.POS (Persero) Singaraja Branch shows the low performance of service officers of PT. POS (Persero) Singaraja Branch can build a bad image at the Post Office. Vice versa, the higher the performance of the service officers of PT POS (Persero) Singaraja Branch was given, it can be added value for the Post Office. In this case, service users will be satisfied with the services provided by the Post Office. This study aims to analyze the effect of Adaptive Selling, Personal Selling, Selling Experience, and Service Personnel Performance at PT. Pos (Persero) Singaraja Branch. This research was conducted using a quantitative method (questionnaire) with a sample of 42 respondents. The data analysis technique used in this research is Structural Equation Modeling (SEM) with Partial Least Square (PLS). Based on the data of the coefficient of determination, the value of the R-Square analysis on the Performance of Manpower Services is 96.7%. The performance produced by PT. POS (Persero) Singaraja Branch is the result of the work of a group of people at the post office, both the service personnel of PT. POS (Persero) Singaraja Branch can provide customer satisfaction, increasing customer retention. It can be said that the increase in Adaptive Selling means the better the performance of the service personnel, the better the service performance, the better the selling experience, and the better the performance of the service personnel.